Fine-mapping of shotgun template-libraries; an efficient strategy for the systematic sequencing of genomic DNA. - Scholler, P (1995)
To test the effectiveness of ordering shotgun DNA-templates prior to sequence analysis, the 450 kb left arm of yeast chromosome XII was randomly subcloned into a phagemid vector. Clones were ordered by hybridisation to an average map density of one new insert every 125 bp and are currently used for sequencing the chromosomal fragment. An 11.5 kb overlap between the template map and a DNA fragment that had been sequenced earlier allowed an independent evaluation of the strategy's effectiveness. To this end, clones were selected from the map and tag-sequenced from either end, thus comparing the map position with the actual location within the 11.5 kb. Of 65 selected clones, taken mostly at random from a total of 423, 58 mapped on average about a quarter of a clone length around their predicted position, with the other seven being between 0.6 and 1.5 clone length off. 75-86 sequencing reactions on clones selected from the map would have been sufficient for completely sequencing both strands of the 11.5 kb fragment. The results demonstrate the efficacy of such template sorting, considerably assisting sequencing at relatively little cost on the mapping level.